Kreowanie wartości w sporcie – przypadek karteli sportowych - Kowalewski, Marcin; Perechuda, Kazimierz (The value creation in sport. The case of sport cartels, 2008)
There are different factors that have impact on the value creation in professional sport. One of the best structures is a sport cartel. The paper emphasizes the value of a sport club and the value creation in the sport cartels.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 215-221